2021
DOI: 10.3390/ejihpe11030048
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Authoritative and Laissez-Faire Leadership on Thriving at Work: The Moderating Role of Conscientiousness

Abstract: This study empirically investigates the less discussed catalytic effect of personality in the relationship of leadership style and employee thriving at work. The growth and sustainability of the organization is linked with the association of leadership style and employee thriving at the worplace. The objectives of this study are to explore the impact of authoritative and laissez-faire leadership styles and the moderating role of the personality trait of conscientiousness on thriving in the workplace. A sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 95 publications
0
19
2
1
Order By: Relevance
“…However, autocratic and laissez-faire styles of leadership show no significant relationship with work behavior. This result supports Wang, Liu, & Liu (2019); Chen, Davison, Mao, & Wang,(2018);and Shen, Chou, & Schaubroeck (2019); however, the study does not support Iqbal, Abid, Arshad, Ashfaq, Athar, & Hassan (2021) that work behavior and laissez-faire style of leadership has a significant relationship. The result of the study has both practical and theoretical implications.…”
Section: Demographic Variablescontrasting
confidence: 59%
“…However, autocratic and laissez-faire styles of leadership show no significant relationship with work behavior. This result supports Wang, Liu, & Liu (2019); Chen, Davison, Mao, & Wang,(2018);and Shen, Chou, & Schaubroeck (2019); however, the study does not support Iqbal, Abid, Arshad, Ashfaq, Athar, & Hassan (2021) that work behavior and laissez-faire style of leadership has a significant relationship. The result of the study has both practical and theoretical implications.…”
Section: Demographic Variablescontrasting
confidence: 59%
“…This shows that changes in leadership style influence changes in employee motivation. Another study by Ahmed Iqbal, Abid, Arshad, Ashfaq, Athar, and Hassan (2021) highlighted that laissez-faire leadership style is associated with thriving at work among employees in Pakistan from varying sectors. However, Robert and Vandenberghe (2022) found that laissez-faire leadership reduced positive mental health and increased depression symptoms.…”
Section: Leadership Stylementioning
confidence: 99%
“…A study by Iqbal et al (2021) explored the impact of authoritative and laissez-faire leadership styles and the moderating role of the personality trait conscientiousness in workplace flourishing. The results of the study indicated that the correlation between authoritative and laissez-faire leadership styles had a positive impact on employee job enjoyment.…”
Section: Laissez-faire Stylementioning
confidence: 99%
“…In addition, this style also supports innovation and creativity, as well as the freedom to make decisions without permission. Iqbal et al (2021) showed that authoritative and laissez-faire leadership styles have a positive impact on employee job satisfaction, where the personality trait conscientiousness plays a thriving moderating role.…”
Section: The Data Inmentioning
confidence: 99%